1984
DOI: 10.1246/cl.1984.1587
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURE OF ISOCHAMAEJASMIN FROM STELLERA CHAMAEJASME L.

Abstract: A new C-3/C-3″-biflavanone named isochamaejasmin has been isolated from Stellera chamaejasme L. (Thymelaeaceae) and its structure has been elucidated by spectroscopic and chemical methods. Furthermore, the stereochemistry of some C-3/C-3″-biflavanones including isochamaejasmin was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…1) and 29 known flavonoids. By comparing physical and spectroscopic data with reported data, the 29 known compounds were identified as chamaechromone (4), 6) neochamaejasmin B (5), 7) neochamaejasmin A (6), 7) 7-methoxy neochamaejasmin A (7), 8) daphnodorin A (8), 9,10) daphnodorin B (9), 9,10) daphnodorin C (10), 10,11) dihydrodaphnodorin B (11), 12) daphnodorin I (12), 13) daphnodorin J (13), 12) afzelechin (14), 14) epiafzelechin (15), 15,16) farrerol (16), 17) naringenin (17), 18) sakuranetin (18), 19) sakuranin (19), 20) genkwanin (20), 21) apigenin (21), 22) kaempferol (22), 23) luteolin (23), 24) Chrysoeriol (24), 25) 7,4Ј-dimethylether-luteolin (25), 21) luteolin-5-O-b-glucoside (26), 26) 5,7,4Ј-trihydroxy-3Ј-methoxyflavone (27), 27) diosmetin (28), 28) 5,3Ј,4Ј-trihydroxy-7-methoxyflavone (29), 29) genk wanin-5-O-b-glucopyranoside (30), 29) 30) and yuankanin (32). 31 (Table 1) were very similar to those of 5-methoxy-2,8-bis-(3,4-dimethoxyphenyl)-2,3-cis-7,8-trans-3,4,6,7-tetrahy...…”
Section: Notementioning
confidence: 99%
“…1) and 29 known flavonoids. By comparing physical and spectroscopic data with reported data, the 29 known compounds were identified as chamaechromone (4), 6) neochamaejasmin B (5), 7) neochamaejasmin A (6), 7) 7-methoxy neochamaejasmin A (7), 8) daphnodorin A (8), 9,10) daphnodorin B (9), 9,10) daphnodorin C (10), 10,11) dihydrodaphnodorin B (11), 12) daphnodorin I (12), 13) daphnodorin J (13), 12) afzelechin (14), 14) epiafzelechin (15), 15,16) farrerol (16), 17) naringenin (17), 18) sakuranetin (18), 19) sakuranin (19), 20) genkwanin (20), 21) apigenin (21), 22) kaempferol (22), 23) luteolin (23), 24) Chrysoeriol (24), 25) 7,4Ј-dimethylether-luteolin (25), 21) luteolin-5-O-b-glucoside (26), 26) 5,7,4Ј-trihydroxy-3Ј-methoxyflavone (27), 27) diosmetin (28), 28) 5,3Ј,4Ј-trihydroxy-7-methoxyflavone (29), 29) genk wanin-5-O-b-glucopyranoside (30), 29) 30) and yuankanin (32). 31 (Table 1) were very similar to those of 5-methoxy-2,8-bis-(3,4-dimethoxyphenyl)-2,3-cis-7,8-trans-3,4,6,7-tetrahy...…”
Section: Notementioning
confidence: 99%
“…1) The 1 H-NMR spectrum of 1 ( Table 1) )] suggested that the linkage of the two flavanones was only at the C-3/C-3Љ positions, which was confirmed by comparison of the 1 H-and 13 C-NMR data of 1 with those of known C-3/C-3Љ biflavanones. [4][5][6] The HMBC correlations of one methoxyl group ( (Table 1), IR and UV data suggested 2 to be a C-3/C-3Љ biflavanone like 1, and its structure was highly symmetric, which was also indicated by the EI-MS [m/z 570 (M …”
mentioning
confidence: 93%
“…4) However, the chirality of C-3/C-3Љ remains uncertain, like those known biflavanones. 1,[4][5][6] In previous studies, the meso-form and d-or l-form biflavanones as 2 and chamaejasmenin B were commonly reported, such as isochamaejasmin (mesoform) 7) and chamaejasmenin (l-form), 8) isoneochamaejasmin A (meso-form) 9) and neochamaejasmin A (d-form) 5) isolated from the same plant. The structure of 2 was thus established to be [3,3Ј-Bi-4H-1-benzopyran]-4,4Ј-dione, 2,2Ј,3,3Ј-tetrahydro-5,5Ј,7Ј,7-tetrahydroxy-2,2Ј-bis(4-methoxyphenyl)-(meso), and named isochamaejasmenin B.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Stellera chamaejasme L., a traditional Chinese medicine, is widely used for the treatment of scabies, ringworm, stubborn skin ulcers, chronic tracheitis, and liver and lung cancers in China and in other Asian countries (Niwa et al, 1984;Yang, 1993). Pharmacological studies have revealed that S. chamaejasme L. possesses multiple bioactivities, including antiviral, antitumor, antimitotic, antifungal, and immunomodulating activities (Yoshida et al, 1996;Endo et al, 1998;Yang et al, 2005;Liu and Zhu, 2012).…”
Section: Introductionmentioning
confidence: 99%